Enhancement Strategies for Visual Arts Online Learning through Community of Inquiry - Rahina Nugrahani; Wandah Wibawanto; Ratih Ayu Pratiwinindya; Arif Ardy Wibowo (AL-ISHLAH: Jurnal Pendidikan, 2023)
The demands and the need to be able to learn various cutting-edge techniques and media in the creation of visual arts, require students to be able to absorb a number of information combined with an intuitive understanding of things that are relevant in every situation. Amidst the COVID-19 global pandemic, various virtual learning communities initiated a trend of visual arts learning. This study aims to reveal the online Community of Inquiry (hereinafter, CoI) learning model that takes place in virtual learning communities in Indonesia. The method of the investigation was a qualitative virtual ethnography approach involving 24 members from two virtual learning communities in Indonesia. Understanding their learning experience was achieved through interviews, participatory observation, and assessment of the participants’ artworks that had been produced during the learning process. Results revealed that the experience of creating visual arts through an online community of inquiry learning had had a positive impact on creation and appreciation activities. By studying how the visual arts learning process takes place in virtual learning communities, we can contribute to ensuring the success of the ongoing community of inquiry model for online learning and suggest comparable tactics to raise the standard of visual arts education online.